PERMAINAN LEMPAR DADU SEBAGAI MEDIA PEMBELAJARAN BINA DIRI KESEHATAN ANAK DOWN SYNDROMEE - Yovita Eka Ratna Kumala; Wafi Nur Muslihatun (Sistem Informasi, 2017)
Down syndrome is a genetic disorder known as trisomy 21 and is most common. Down syndrome children have visual processing skills are better, but almost all children who suffer from this disorder can not read, write and take care of herself. This study aims to prove whether Roll dice game method can improve the ability of children with Down syndrome do Bina Yourself Healthy at SLB Mardi Mulya Kretek, Bantul, Yogyakarta. This study is a game of throwing dice experiment with the design of one group pretest-posttest. The instruments used were throwing dice game instruction with the words, cartoons and images and test viewing capabilities and perform the instructions mentioned on the dice. Data were analyzed descriptively calculate the percentage of children's success. The results showed toss the dice with the instructions of the original image (photo) provides the capability to mention children and do the instruction with the highest success rate (95.23%) compared to the instruction by writing (14.28%) and cartoons (66.67%).